Intelligent manufacturing and materials : selected peer-reviewed full text papers from the International Conference on Intelligent Manufacturing and Materials (IMM 2021) - Bratan, Sergey; Roshchupkin, Stanislav (Materials Science Forum ;, 2021)
Selected peer-reviewed full text papers from the International Conference on Intelligent Manufacturing and Materials (IMM 2021) Selected, peer-reviewed papers from the International Conference on Intelligent Manufacturing and Materials 2021 (IMM 2021), March 1-5, 2021, Yalta, Russian Federation.